Patients' adherence-related beliefs about inhaled steroids: application of the Chinese version of the Beliefs about Medicines Questionnaire-specific in patients with asthma. (3rd March 2020) - Cai, Qingqing; Ye, Ling; Horne, Robert; Bi, Jing; Xu, Qing; Ye, Xiaofen; Yang, Aifang; Jin, Meiling; Li, Xiaoyu; Lv, Qianzhou
Abstract: Objective : The main objective of the present study is to evaluate the psychometric properties of the Chinese version of Beliefs about Medicines Questionnaire-specific among asthma patients; and to assess the association between patients' belief and adherence to inhaled corticosteroid therapy. Methods : A cross-sectional survey was carried out in the asthma clinic of Zhongshan Hospital, to Fudan University (Shanghai, China) between April 2016 and March 2018. The Beliefs about Medicines Questionnaire-specific was translated into Chinese according to international guidelines. Internal consistency, test–retest reliability, and confirmatory factor analysis were calculated to validate the Beliefs about Medicines Questionnaire-specific. The relationship between the adherence and the belief subscale were assessed using Kruskal–Wallis test. Results : Two hundred and seventeen patients were recruited in this study. The Beliefs about Medicines Questionnaire-specific was deemed reliable based on the results of Cronbach's alpha coefficient and test–retest intraclass correlation coefficient (ICC, ICC= 0.759). Confirmatory factor analysis showed acceptable model fit for the two-factor model. Patients' compliance was closely related to their belief about inhaled corticosteroid. The adherence rates were highest for the accepting groups, and lowest for the skeptical groups. Higher adherence was significantly associated with higher necessity-concerns differential ( p  = .001) and lower concern ( p  = .004). Conclusions : The Chinese version of the Beliefs about Medicines Questionnaire-specific can be used as a reliable tool by the clinicians to identify beliefs and behaviors of individual to improve adherence in Chinese patients.